2008
DOI: 10.1613/jair.2611
|View full text |Cite
|
Sign up to set email alerts
|

Completeness and Performance Of The APO Algorithm

Abstract: Asynchronous Partial Overlay (APO) is a search algorithm that uses cooperative mediation to solve Distributed Constraint Satisfaction Problems (DisCSPs). The algorithm partitions the search into different subproblems of the DisCSP. The original proof of completeness of the APO algorithm is based on the growth of the size of the subproblems. The present paper demonstrates that this expected growth of subproblems does not occur in some situations, leading to a termination problem of the algorithm. The problemati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 20 publications
1
19
2
Order By: Relevance
“…APO uses the least number of NCCCs, cycles, and messages with NAPO using slightly more. These results seem to contradict the findings of presented by Grinshpoun and Meisels [5] who reported that APO used more NCCCs on medium density problems across various levels of constraint tightness. The discrepancy between these results can likely be explained by the difference in the experiments that were conducted.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…APO uses the least number of NCCCs, cycles, and messages with NAPO using slightly more. These results seem to contradict the findings of presented by Grinshpoun and Meisels [5] who reported that APO used more NCCCs on medium density problems across various levels of constraint tightness. The discrepancy between these results can likely be explained by the difference in the experiments that were conducted.…”
Section: Resultscontrasting
confidence: 99%
“…We refer the reader to [9] and [5] for the complete details of the proofs for APO. Here is a basic outline of the proof for NAPO:…”
Section: Soundness and Completenessmentioning
confidence: 99%
“…APO uses the least number of NCCCs, cycles, and messages with NAPO using slightly more. These results seem to contradict the findings of presented by Grinshpoun and Meisels [8] who reported that APO used more NCCCs on medium density problems across various levels of constraint tightness. The discrepancy between these results can likely be explained by the difference in the experiments that were conducted.…”
Section: Resultscontrasting
confidence: 99%
“…The reader is referred to [14] and [8] for the complete details of the proofs for APO. The original proof of APO's soundness and completeness was originally discovered to be incorrect in early 2005.…”
Section: Soundness and Completenessmentioning
confidence: 99%
See 1 more Smart Citation